Larung Sesaji Gunung Kelud, Tradisi Tak Benda yang Penuh Makna - Hadi, Hanifah Afnan (DIWANGKARA: Jurnal Pendidikan, Bahasa, Sastra dan Budaya Jawa, 2025)
The tradition of Larung Sesaji Gunung Kelud is a tradition that is still practiced in Sugihwaras Village, Ngancar District, Kediri Regency. The tradition of larung sesaji gunung kelud is held every year on the 1st of Suro. This tradition stems from the habits of the people of Sugihwaras Village, Ngancar Sub-District, Kediri Regency who make thanksgiving every time they get good things, then there is a proposal to unite the ceremonies at the same time so that the Larung Sesaji Gunung Kelud Tradition was born which is still being carried out today. This research was conducted to document the intangible culture of Kediri Regency. This research was conducted by interview method with one of Sugihwaras villagers and literature study of previous works related to larung sesaji gunung kelud. The results showed that the symbols in the tradition of larung sesaji of Mount Kelud contain important meanings for the people of Sugihwaras Village, this is what makes the tradition of larung sesaji of Mount Kelud still exist today.